2005
DOI: 10.1111/j.1600-051x.2004.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐gingivitis efficacy of a stabilized 0.454% stannous fluoride/sodium hexametaphosphate dentifrice

Abstract: The results demonstrate that use of the stabilized 0.454% stannous fluoride/sodium hexametaphosphate dentifrice over a 6-month period provided statistically significant reductions in gingivitis, gingival bleeding, and plaque when compared with a negative control dentifrice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 26 publications
4
32
0
3
Order By: Relevance
“…Są to badania przeprowadzone wyłącznie w ośrodkach amerykańskich, zawsze z udziałem centrum naukowego producenta pasty ze stabilizowanym fluorkiem cyny. Do metaanalizy wpły-wu pasty z fluorkiem cyny na ograniczenie wskaź-nika płytki nazębnej po 6 miesiącach szczotkowania włączono 4 badania [15][16][17][18], w których oceniano łącznie w punkcie końcowym 336 osób w grupie badanej oraz 362 w grupie kontrolnej. W celu metaanalizy wpływu pasty z fluorkiem cyny na zmniejszenie zapalenia dziąseł po 6 miesią-cach szczotkowania włączono 2 badania [17,18], w których na końcu obserwacji oceniano 128 osób w grupie badanej oraz 130 w grupie kontrolnej.…”
Section: Wynikiunclassified
See 2 more Smart Citations
“…Są to badania przeprowadzone wyłącznie w ośrodkach amerykańskich, zawsze z udziałem centrum naukowego producenta pasty ze stabilizowanym fluorkiem cyny. Do metaanalizy wpły-wu pasty z fluorkiem cyny na ograniczenie wskaź-nika płytki nazębnej po 6 miesiącach szczotkowania włączono 4 badania [15][16][17][18], w których oceniano łącznie w punkcie końcowym 336 osób w grupie badanej oraz 362 w grupie kontrolnej. W celu metaanalizy wpływu pasty z fluorkiem cyny na zmniejszenie zapalenia dziąseł po 6 miesią-cach szczotkowania włączono 2 badania [17,18], w których na końcu obserwacji oceniano 128 osób w grupie badanej oraz 130 w grupie kontrolnej.…”
Section: Wynikiunclassified
“…Na rycinie 2 pokazano na wykresie leśnym wpływ szczotkowania pastą ze stabilizowanym fluorkiem cyny na zmniejszenie zapalenia dziąseł w porównaniu z pastą z monofluorofosforanem sodu. Stwierdzono istotne większe zmniejszenie intensywności stanu zapalnego wyrażanego za pomocą wskaźnika MGI po użyciu SnF 2 (D = 0,38 ± ± 0,1, p = 0,0000) i oba badania [17,18] potwierdziły jego przewagę w działaniu przeciwzapalnym w odniesieniu do produktów z monofluorofosforanem sodu. W ocenie Mankodiego et al [17] zakres redukcji intensywności zapalenia dziąseł wynosił 21,7%, w ocenie Mallatta et al [18] 16,9%.…”
Section: Wynikiunclassified
See 1 more Smart Citation
“…1 This study, the world's largest to date with the longest recorded microbiological followup period of 24 months, demonstrates that the PERIOBLAST treatment successfully eradicated periodontal disease in 100% of 2,683 patients.…”
mentioning
confidence: 99%
“…This powerful ingredient gives Oral-B's Pro-Expert toothpaste a long-lasting antimicrobial action, which fights plaque and consequently gum problems. A sixmonth trial by Mankodi et al 1 concluded that dentifrice containing stabilised stannous fluoride had a statistically significant effect on the control and prevention of gingivitis. It inhibits antimicrobial growth as well as reducing the ability of bacteria to 'stick' to tooth and gum surfaces.…”
mentioning
confidence: 99%